Correlation of grain orientations and the thickness of gradient MoS2 films. Issue 54 (22nd October 2021) - Chang, Hui-Ping; Hofmann, Mario; Hsieh, Ya-Ping; Chen, You-Sheng; Lin, Jauyn Grace
Abstract : Correlation of grain orientations, film thickness, and A1g /E12g ratios extracted from the Raman spectra of gradient MoS2 . Abstract : In this study, we synthesized gradient MoS2 films with a home-made suspended mask and characterized them by transmission electron microscopy (TEM) and Raman spectroscopy. The advantage of using gradient films is to simultaneously produce numerous samples under the same growth condition but with different thicknesses. The cross-sectional TEM images and their Fourier transform spectra revealed the thickness dependency of the grain orientations for synthetic MoS2 films. Combining the TEM results and the data of Raman A1g and E12g peaks, we found the correlation between the grain orientation and the A1g /E12g peak area ratio. We demonstrated the potential of using the non-polarized Raman Spectroscopy to characterize the grain structures of synthetic MoS2 films.